2021
DOI: 10.3389/fphar.2021.727275
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Dihydroartemisinin on the Proliferation and Migration of Melanoma Cells and Experimental Lung Metastasis From Melanoma in Mice

Abstract: Melanoma is aggressive and can metastasize in the early stage of tumor. It has been proved that dihydroartemisinin (DHA) positively affects the treatment of tumors and has no apparent toxic and side effects. Our previous research has shown that DHA can suppress the formation of melanoma. However, it remains poorly established how DHA impacts the invasion and metastasis of melanoma. In this study, B16F10 and A375 cell lines and metastatic tumor models will be used to investigate the effects of DHA. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The most optimal therapeutic strategy is considered to involve integrating most of the immune subpopulations without causing significant toxicity. In our previous study, we found that CD8 + CTL cells were effective at inducing the apoptosis of melanoma cells in mice with metastatic cancer, as inhibition of the immunosuppressive effect of the Treg cell can impress melanoma in situ [ 5 , 6 ]. It has been demonstrated that M1 macrophages expressed high levels of CD86, MHC II and B7 and mediated anti-tumor effects by secreting high-level cytokines (such as IL-12, IL-23, IL-1 and IL-6) and chemokines (MCP-1, CCL3, CXCL9, CXCL10, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The most optimal therapeutic strategy is considered to involve integrating most of the immune subpopulations without causing significant toxicity. In our previous study, we found that CD8 + CTL cells were effective at inducing the apoptosis of melanoma cells in mice with metastatic cancer, as inhibition of the immunosuppressive effect of the Treg cell can impress melanoma in situ [ 5 , 6 ]. It has been demonstrated that M1 macrophages expressed high levels of CD86, MHC II and B7 and mediated anti-tumor effects by secreting high-level cytokines (such as IL-12, IL-23, IL-1 and IL-6) and chemokines (MCP-1, CCL3, CXCL9, CXCL10, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…However, surgical resection is limited and cannot effectively treat metastatic tumors. Radiotherapy and chemotherapy have drug toxicity and a high cost (5,6). Therefore, it is important to prevent melanoma through lifestyle.…”
Section: Introductionmentioning
confidence: 99%